Hearing Improvement in Patients Undergoing Underlay Technique in Myringoplasty - Sarwar, Muhammad Haris; Gohar, Muhammad Saeed; Afridi, Arshad Ullah (Biological and Clinical Sciences Research Journal, 2025)
Chronic tympanic membrane perforations can result in significant conductive hearing loss. Myringoplasty, particularly the underlay technique, is a commonly performed surgical procedure to restore membrane integrity and improve hearing outcomes. Evaluating the effectiveness of this technique is vital for evidence-based clinical decision-making. Objective: The present aim is to determine the frequency of Hearing improvement in patients undergoing the underlay technique in myringoplasty. Methods: After the ethical approval from the institutional review board, this Descriptive case series study was conducted at the Department of ENT, Shalimar Hospital, Lahore, from August 01, 2024, to February 01, 2025. Through non-probability consecutive sampling, 150 patients aged 18-60, both genders, with Central tympanic membrane perforations were included in the present study. Results: In terms of hearing loss and air-bone gap (ABG) before and after surgery, significant improvements were observed, as detailed in Table 2. Pre-operatively, the average hearing loss was 55.9 ± 13.8 dB, which improved to 41.2 ± 14.1 dB post-operatively (p < 0.0001). Similarly, the average pre-operative air-bone gap was 20.01 ± 6.03 dB, which decreased to 14.5 ± 6.4 dB after surgery, indicating a significant reduction in the gap (p < 0.0001). One hundred twenty-one patients (80.7%) experienced hearing improvement, while 29 (19.3%) did not. Conclusion: The underlay approach in myringoplasty surgery brings substantial auditory benefits by reducing both disability degrees and air-bone gaps after surgery is complete.